The effect of exercise on urinary gamma-glutamyl transferase and protein levels of volleyball players - Ayca, B.; Sener, A.; Apikoglu Rabus, S.; Oba, R. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: Postexercise proteinuria and increased urinary gamma-glutamyl transferase (GGT) levels can be indicative of exercise-induced renal damage. In the literature, there exists numerous studies on exercise-induced proteinuria; but studies investigating the effects of exercise on urinary GGT levels are quite few. We aimed to evaluate the effects of exercise on renal function, expressed through the exercise-induced differences in urinary GGT, creatinine and protein levels. Methods: The study was performed on 12 female and 12 male volleyball players of the same sports club. Urine samples collected before and 1 h after the exercise were analyzed for urinary GGT, creatinine and protein amounts. Results: No statistically significant difference was observed between pre- and postexercise urinary GGT levels (U/L and U/g creatinine) of female and male volleyball players (P>0.05). A significant exercise-induced increase in urinary protein excretion was observed for the male players, while a significant exercise-induced increase in urinary creatinine excretion was observed for the female players (P<0.05). When urinary GGT levels (U/L) were compared separately for setters and spikers, it was observed that female players had no significant difference, while male spikers had a statistically significant exercise-induced increase in the urinary GGT levels (U/L) (P<0.05). Conclusions: We suggest that the insignificance of the exercise-induced increases in the urinary parameters could be due to the relatively short-course of the exercise and the timing of postexercise urine collection. A comprehensive study performed on more subjects could yield results that are more significant.